The impacts of climate change on agricultural production, land use and economy of the Legal Amazon region between 2030 and 2049 - Tarik Marques do Prado Tanure; Diego Nobuhiko Miyajima; Aline Souza Magalh\~aes; Edson Paulo Domingues; Terciane Sabadini Carvalho (EconomiA, 2020)
Global warming and climate impact on agricultural output, land use and food production. This paper seeks to verify the economic impacts of climate change in the Legal Amazon region, especially on agricultural production, land use, GDP and job creation. We employ the Computable General Equilibrium (CGE) model, REGIA - Inter-regional General Equilibrium Model for the Brazilian Legal Amazon, to assess changes in agricultural production and land use in the region due to climate change scenarios proposed by the IPCC (Intergovernmental Panel on Climate Change). The results indicate a drop in economic indicators in the Legal Amazon leading to a loss in real GDP in the order of 1.18% in 2049 due to decrease in production and employment in the agricultural sector. Deforestation will increase due to the gradual replacement of pasture areas by crop fields. Such changes are not homogeneous in the space, affecting more the states of Mato Grosso, Tocantins and Pará, whose economy are dependent upon agriculture.
Keywords: R11; R13; 330; Climate Change; Food Production; Legal Amazon; Computable General Equilibrium